2022
DOI: 10.3390/ijerph19074290
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Professionals’ Knowledge and Behaviors Regarding Drug–Dietary Supplement and Drug–Herbal Product Interactions

Abstract: Given the widespread use of dietary supplements (DS) and herbal products (HP), healthcare professionals (HCPs) will increasingly encounter patients who use these preparations with conventional drugs and who need their services to reduce the consequences of adverse therapeutic outcomes. The aim of our survey was to assess the knowledge and behaviors of HCPs regarding the risk of potential drug–dietary supplement (DDSIs) and drug–herbal product (DHPIs) interactions. This cross-sectional survey collected data via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 64 publications
(64 reference statements)
0
14
0
Order By: Relevance
“…Most studies used a correlational/comparative design. Specifically, 37 followed a cross-sectional design [ 2 , 7 , 10 , 30 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ] ( Table 1 ) and two followed experimental designs [ 43 , 94 ] ( Table 2 ). Three studies used qualitative methodology [ 95 , 96 , 97 ] and two used mixed-method (qualitative and quantitative) research designs [ 98 , 99 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most studies used a correlational/comparative design. Specifically, 37 followed a cross-sectional design [ 2 , 7 , 10 , 30 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ] ( Table 1 ) and two followed experimental designs [ 43 , 94 ] ( Table 2 ). Three studies used qualitative methodology [ 95 , 96 , 97 ] and two used mixed-method (qualitative and quantitative) research designs [ 98 , 99 ] ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding data collection procedures, most of the data were collected through questionnaires/surveys [ 7 , 10 , 30 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 98 ]. In other studies, data were collected through interviews [ 2 , 61 , 96 , 99 ] and three of these studies used focus groups [ 92 , 95 , 97 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the pharmacy is the most common place to purchase DSs, previous systematic reviews indicated that pharmacist knowledge about DSs is generally without the actual evidence levels of their efficacy, quality, and safety [ 48 , 49 ]. Therefore, pharmacists and other healthcare professionals need continuous education through curriculum enhancement programs and post-graduation training [ 50 ].…”
Section: Discussionmentioning
confidence: 99%